Precision Medicine in Control of Visceral Leishmaniasis Caused by L. donovani - Zijlstra, Eduard E. (Frontiers in Cellular and Infection Microbiology, 2021)
Precision medicine and precision global health in visceral leishmaniasis (VL) have not yet been described and could take into account how all known determinants improve diagnostics and treatment for the individual patient. Precision public health would lead to the right intervention in each VL endemic population for control, based on relevant population-based data, vector exposures, reservoirs, socio-economic factors and other determinants. In anthroponotic VL caused by L. donovani, precision may currently be targeted to the regional level in nosogeographic entities that are defined by the interplay of the circulating parasite, the reservoir and the sand fly vector. From this 5 major priorities arise: diagnosis, treatment, PKDL, asymptomatic infection and transmission. These 5 priorities share the immune responses of infection with L. donovani as an important final common pathway, for which innovative new genomic and non-genomic tools in various disciplines have become available that provide new insights in clinical management and in control. From this, further precision may be defined for groups (e.g. children, women, pregnancy, HIV-VL co-infection), and eventually targeted to the individual level.